Co(iii) protoporphyrin IX chloride in solution: spin-state and metal coordination revealed from resonant inelastic X-ray scattering and electronic structure calculations. Issue 5 (22nd December 2014) - Atak, Kaan; Golnak, Ronny; Xiao, Jie; Pflüger, Mika; Brandenburg, Tim; Winter, Bernd; Aziz, Emad F.
Abstract : The local electronic structure of the cobalt centre-ion of Co(iii ) protoporphyrin IX chloride dissolved in dimethyl sulfoxide (DMSO) liquid solution is studied by resonant inelastic X-ray scattering (RIXS) spectroscopy at the cobalt L-edge. Abstract : The local electronic structure of the cobalt centre-ion of Co(iii ) protoporphyrin IX chloride dissolved in dimethyl sulfoxide (DMSO) liquid solution is studied by resonant inelastic X-ray scattering (RIXS) spectroscopy at the cobalt L-edge. The resulting cobalt 2p partial-fluorescence-yield (PFY) X-ray absorption (XA) spectrum, integrated from RIXS spectra, is simulated for various possible spin-states and coordination of the cobalt centre by using the newly developed density functional theory/restricted open shell single excitation configuration interaction (DFT/ROCIS) method. Comparison between experiment and calculation shows that the cobalt ion (3d 6 electronic configuration) adopts a low-spin state with all six 3d electrons paired, and the cobalt centre is either 5-coordinated by its natural ligands (one chloride ion and four nitrogen atoms), or 6-coordinated, when binding to an oxygen atom of a DMSO solvent molecule. Analysis of the measured RIXS spectra reveals weak 3d–3d electron correlation, and in addition a value of the local HOMO–LUMO gap at the Co sites is obtained.